Diagnostic Value of Cone-Beam Computed Tomography and Digital Periapical Radiography in Detection of Separated Instruments - Ayatollahi, Fatemeh; Tabrizizadeh, Mahdi; Razavi, Hossein; Mowji, Mana (Iranian Endodontic Journal, 2019)
Introduction: File Fracture is one of the most common problems during root canal treatment which can affect treatment procedure and prognosis, so it is important to diagnose and prevent it. The aim of this study was to evaluate and compare the diagnostic value of cone-beam computed tomography (CBCT) and digital periapical radiography for detection of separated instrument retained inside the canal. Methods and Materials: Ninety single-rooted extracted human teeth were selected and randomly divided into 3 groups (n=30). Group 1, separated file #10 at the 2-mm apical third of the root canal; group 2, separated file #35 at the 2-mm apical third of the root canal; and group 3, without a broken file (control group). The teeth were instrumented to size #30 and were shaped to size #55 and then the canals were obturated up to separated instrument, or the working length for the teeth without a separated instrument, with lateral condensation technique. After that all teeth were placed in dry skull, digital radiography and CBCT was taken. After data collection, data was analyzed using SPSS software by means of sensitivity, specificity, positive and negative predictive values, and frequency tables. Results: Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of digital periapical radiography in detection of a fractured file #10 in the canal was 96.7% and 63.3%, 76.7%, 73.1%, 67.6%, 70%, for CBCT, respectively. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of digital periapical radiography in detection of a fracture file #35 in the canal was 93.3%, 96.7%, 96.6%, 93.5% and 95%, and 36.7%, 76.7%, 61.1%, 54.8%, 56.66%, for CBCT, respectively. Conclusion: Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of digital periapical radiography was better than the CBCT technique in both sizes of broken files. Keywords: Broken File; Cone-Beam Computed Tomography; Digital Radiography; Separated Instrument